Exploring the microbial landscape: uncovering the pathogens associated with community-acquired pneumonia in hospitalized patients - Karin Hansen; Karin Hansen; Linda Yamba Yamba; Lisa Wasserstrom; Lisa Wasserstrom; Elisabeth Rünow; Elisabeth Rünow; Tommy Göransson; Anna Nilsson; Jonas Ahl; Jonas Ahl; Kristian Riesbeck; et al. (Frontiers Media S.A., 2023)
ObjectivesThis study aimed to investigate the etiology, clinical features, and outcomes of community-acquired pneumonia (CAP) in adults. Understanding the causative pathogens is essential for effective treatment and prevention.DesignBetween 2016-2018, 518 hospitalized adults with CAP and 241 controls without symptoms were prospectively enrolled. Urine samples were collected for pneumococcal urinary antigen tests and nasopharyngeal swabs for viral and bacterial analysis, combined with routine diagnostic care.ResultsAmong the included CAP patients, Streptococcus pneumoniae was the most common pathogen, detected in 28% of patients, followed by Haemophilus influenzae in 16%. Viruses were identified in 28%, and concurrent viruses and bacteria were detected in 15%. There was no difference in mortality, length of stay, or symptoms at hospitalization when comparing patients with bacterial, viral, or mixed etiologies. Among the control subjects without respiratory symptoms, S. pneumoniae, H. influenzae, or Moraxella catarrhalis were detected in 5-7%, and viruses in 7%.ConclusionStreptococcus pneumoniae emerged as the predominant cause of CAP, followed closely by viruses and H. influenzae. Intriguingly, symptoms and outcome were similar regardless of etiology. These findings highlight the complexity of this respiratory infection and emphasize the importance of comprehensive diagnostic and treatment strategies.Clinical Trial Registration: ClinicalTrials.gov, identifier [NCT03606135].